2011
DOI: 10.2527/jas.2011-3974
|View full text |Cite
|
Sign up to set email alerts
|

Porcine intramuscular fat content and composition are regulated by quantitative trait loci with muscle-specific effects1

Abstract: Intramuscular fat (IMF) storage is a biological process with a strong impact on nutritional and technological properties of meat and also with relevant consequences on human health. The genetic architecture of IMF content and composition phenotypes has been thoroughly studied in pigs through the identification of QTL and the estimation of genetic parameters. A question that has not been elucidated yet is if the genetic determinants of IMF-related phenotypes are muscle specific or, conversely, have broad effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…Fatty acid composition is not uniform across all muscle tissues, as has been shown by comparison of Gluteus medius, Longissimus thoracis and Lumborum muscles in Duroc pigs (Quintanilla et al, 2011) or even in different layers of ham, loin, backfat, and abdominal fat (Monziols et al, 2007). Thus, conclusions drawn for a specific tissue cannot be directly extrapolated to the others.…”
Section: Introductionmentioning
confidence: 85%
“…Fatty acid composition is not uniform across all muscle tissues, as has been shown by comparison of Gluteus medius, Longissimus thoracis and Lumborum muscles in Duroc pigs (Quintanilla et al, 2011) or even in different layers of ham, loin, backfat, and abdominal fat (Monziols et al, 2007). Thus, conclusions drawn for a specific tissue cannot be directly extrapolated to the others.…”
Section: Introductionmentioning
confidence: 85%
“…171,172 Recent studies have suggested that the effect of polymorphisms influencing IM, cholesterol, and fatty acid contents are modulated by several factors related to muscle location, metabolism and function. 173 Stearoyl-CoA desaturase (SCD1) activity has been shown to increase with higher fat accumulation in skeletal muscle in humans and animals possibly related to the SNPs in 3¢-UTR that contains G > A and C > T in the bovine gene (which are also highly conserved in humans and pigs). 141 Furthermore, the polymorphism in the PPARg (TA haplotype favorable over CG haplotype) upstream transcriptional regulatory region has been associated with higher IM.…”
Section: Genetic Variations/qtl and Epigenetic Changes Associated Witmentioning
confidence: 99%
“…Few publications can be found in literature reporting QTLs responsible for some productive traits in Japanese quail (Tavaniello et al, 2014); QTL studies for meat quality traits as muscle cholesterol content or FA composition have not been performed in poultry species. The only results reported in AnimalQTLdb concern pigs (Malek et al, 2001;Thomsen et al, 2004;Quintanilla et al, 2011). In light of this, the present study was undertaken to evaluate the effect of different lines (meat-type and egg-type quails), cross (meat-type x egg-type quails; F 0 x F 1 ) and sex (males and females) on total lipid, FA composition and cholesterol content of meat from adult Japanese quails.…”
Section: Introductionmentioning
confidence: 99%